Equity market and exchange rate volatility in Asean 5 countries / Prof Madya Dr Mazila Md Yusuf and Hamisah Abd Rahman - Md Yusuf, Mazila; Abd Rahman, Hamisah (Research Management Institute (RMI), 2013)
Foreign exchange rates have been highly volatile since the abandonment of the fixed exchange rate system in 1973. The volatility of the exchange rate is the source of exchange rate risk and this has certain implications on the economic growth of a country. This is because a rise in exchange rate volatility is said to deters multinational companies and foreign investors from engaging in international activities. When currency appreciates, the sales and profits of exporters will decline and stock prices will drop due to the fact that exporters lose their international competitiveness. On the other hand, importers' competitiveness in domestic market will increase which would lead to the increase in profit and stock prises. The scenarios would be opposite in the case of currency depreciation. Equity markets and foreign exchange markets have been regarded as sensitive segments of the financial market due to the impact of any policy changes gets quickly reflected in both markets. The issue of inter-relation between stock returns and exchange rates has often been discussed by economists since they both play important roles in influencing the development of a country's economy. Changes in stock prices may influence the movements in the exchange rate, via firm's portfolio adjustments [1]. Due to this dynamic interrelationship between the two markets has prompted researchers, policy makers and analysts to carry out detailed analyses of this relationship.